THE EFFECTS OF SPAMMING AND INFORMATION OVERLOAD ON ONLINE PURCHASE DECISION MAKING IN MANADO - Paat, Mario (Universitas Sam Ratulangi, 2013)
The growth of e-commerce and electronic media users rapidly increase, but lack of knowing on how people make decision to buy products through internet cannot be denied. The fact is that many vendors that sell their products on internet through beautiful and attractive website with attractive and beautiful images on it. They strive to make their websites look good on people’s eyes to persuade them to explore their website while putting some information or description of products to let people choose the products offered. As an effort to gain loyal consumers, sellers realize that buyers need information. The aim of this study is to analyze the effects of spamming and information overload on online purchase decision making in Manado. Research method that is implemented in this study is qualitative research where it is to figure out the effects of spamming and information overload on online purchase decision making and to see which of them that affects the most. The population of this study is young people in Manado who have been experiencing and or had experienced online shopping. There are 8 respondents as research samples. The result of this study shows that spamming does not affect people in making decision to buy products online, while information overload affects people in making decision to buy products online. Keywords: information, information overload, spamming